INTERNATIONAL TRADE, GLOBALIZATION AND NIGERIAN ECONOMY - Odo, Cosmas; Ozoemenam, Kenneth N.; Edeh, Kingsley N. (Archives of Business Research, 2021)
Protagonists of free trade such as the World Bank and IMF are loud in proclaiming the virtues of international trade and globalization. They are quick to point out that granting free rein to these concepts would not only lead to optimal resource allocation but also engender growth in global economy. This paper sought to probe the veracity of these claims in the context of a developing economy like Nigeria. The paper first clears up conceptual issues involved and later cast the operations of these phenomena within the Nigerian economic setting. It was found that whereas industrial countries, in joint operation with their multinational corporations, may have benefited immensely from the opportunities created by international trade and globalization, developing countries, characterized by weak technological base and unfavourable macro-economic factors, have hitherto benefitted minimally, but her losses far outweigh her gains such that she could rightly be characterized as a net loser in the competition. It therefore argues that countries like Nigeria should protect their domestic markets from the negative impact of foreign trade and globalization. It however recommends that Nigeria should adopt a selective technological transfer that fits into her domestic need for economic diversification via private sector-led initiatives.